2009
DOI: 10.1097/meg.0b013e32831bed96
|View full text |Cite
|
Sign up to set email alerts
|

Safer sedation practice may not translate into improvements in endoscopic outcomes

Abstract: Although protocols to enhance safer sedation practice substantially reduced sedation doses used; this did not, however, translate into improved endoscopic outcomes. Moreover, incomplete procedures because of poor tolerance increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…9, Seite 41). Ein Grund für Todesfälle bei oder nach Endoskopien unter Sedierung könnten zu hohe Dosierungen der verwendeten Substanzen sein [77,78]. In einer Unter-suchung mittels zwei Audits im Abstand von zwei Jahren wurde an insgesamt über 14 000 Patienten in einer Single-Center Studie aus England gezeigt, dass durch die Einführung von Leitlinien zur Sedierung in der Endoskopie die verwendeten Dosierungen von Sedativa und Analgetika zum Teil deutlich reduziert wurden.…”
Section: Empfehlung Anästhesie/intubationunclassified
See 1 more Smart Citation
“…9, Seite 41). Ein Grund für Todesfälle bei oder nach Endoskopien unter Sedierung könnten zu hohe Dosierungen der verwendeten Substanzen sein [77,78]. In einer Unter-suchung mittels zwei Audits im Abstand von zwei Jahren wurde an insgesamt über 14 000 Patienten in einer Single-Center Studie aus England gezeigt, dass durch die Einführung von Leitlinien zur Sedierung in der Endoskopie die verwendeten Dosierungen von Sedativa und Analgetika zum Teil deutlich reduziert wurden.…”
Section: Empfehlung Anästhesie/intubationunclassified
“…Das Outcome (z. B. Mortalität) änderte sich jedoch nicht signifikant, gleichzeitig kam es aber zu einem Anstieg an nicht vollendeten Untersuchungen aufgrund mangelnder Patientenmitarbeit [78]. Eine andere Untersuchung an 585 Patienten, die koloskopiert wurden, fand keinen Einfluss der Sedierungstiefe (moderat vs. tief) auf die Untersuchungsqualität bezüglich Adenomerkennung bzw.…”
Section: Empfehlung Anästhesie/intubationunclassified
“…However, increasing the depth of sedation, achieved by raising the dose of the various substances, also increases the incidence of unexpected/unwanted side effects (see dose recommendations in the product information of various manufacturers and • " Table 9). One reason for observed deaths during or after endoscopies could be excessive dosing of the used medications [82,83]. One study, which included 2 audits within 2 years, including more than 14 000 patients in a single centre in England, showed that the dosages of sedatives and analgesics were in part markedly reduced by the implementation of a sedation guideline for endoscopy.…”
Section: Commentsmentioning
confidence: 99%
“…However, the outcome (e. g. mortality) did not change significantly. Simultaneously, there was an increase in incomplete examinations as a result of reduced patient compliance [83].…”
Section: Commentsmentioning
confidence: 99%
“…For example, the last multi‐regional audit in England was over 30 years ago and identified high cardiovascular risks associated with over‐sedation 12,13 . Sedation practices have since improved though this may not have improved safety 14 and the population undergoing endoscopy has changed with increasing age and comorbidity, 15 so updated measures are needed. More recent studies suggest that respiratory adverse outcomes are still increased following day‐case gastroscopies, particularly in those with existing respiratory disease, 8,16 but can be criticised either for their limited size, or for reliance upon the report of complications back to endoscopists after discharge.…”
Section: Introductionmentioning
confidence: 99%